Socio-Economic Situation of Middle Urals in the First Post-Crisis Year 1999 (according to Regional and Municipal Statistics) - V. N. Mamyachenkov; D. V. Reznichenko (Научный диалог)
The base of the study was a set of statistical data, both stored in the personal archives of the authors and published in the form of statistical collections, as well as scientific literature. The analysis of the socio-economic situation of the Sverdlovsk Region (Middle Urals) in the first year after the systemic economic crisis of August 1998 is carried out. The scientific novelty of the research is seen in the fact that the reconstruction of the socio-economic state of the region was carried out in one of the turning years of its history. New previously unpublished materials are being introduced into scientific circulation. It is noted that the financial crisis of 1998 dealt a powerful blow to the socio-economic life of the Russian Federation. It is stated that it was only the ultimate aggravation of the extreme socio-economic situation already at that time. It is stated that 1999 was a year of turning point in general and gradual transition to the systematic development of market relations. It is declared that during this year there were significant positive changes in the industry and the budgetary sphere of the region. It is claimed that there was a deep stagnation in agriculture. The conclusion is made about the ambiguity of the crisis consequences for different categories of the population.